2013
DOI: 10.1159/000343539
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Regulation of Cell Growth and Angiogenesis by Inositol Hexaphosphate in Bladder Cancer

Abstract: Background: Inositol Hexaphosphate (IP6) is a naturally occurring polyphosphorylated carbohydrate that is found in food sources high in fiber content. We hypothesized that IP6 would inhibit the cell growth rate of bladder cancer in vitro. Methods: T24 and TCCSUP bladder cancer cell lines were treated with titrating doses of IP6 (0.3, 0.6 and 0.9 mM/well). Cell viability and vascular endothelial growth factor levels were measured. Results: Significant reductions (p < 0.001) in cellular growth were noted in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…However, IP6 is best appreciated for its anti-cancer properties, resulting from its capability of reduction cell proliferation, apoptosis induction, and tumor metastasis inhibition [8,9,10]. The outcomes of many experiments have shown that IP6 broad spectrum activities involve its impact on various intracellular signaling pathways, such as PI3K/AKT (Phosphatidylinositol-3 Kinase/AKT Serine/Threonine Kinase 1) [11,12] and expression of genes encoding key cellular proteins like p53, p21, p27, BCL-2, and MMPs [13,14,15,16,17,18,19]. The anti-cancer properties of dietary IP6 have previously been demonstrated by both in vitro and in vivo experimental cancer models including, prostate, breast, bladder, and colon [10,12,13,15,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…However, IP6 is best appreciated for its anti-cancer properties, resulting from its capability of reduction cell proliferation, apoptosis induction, and tumor metastasis inhibition [8,9,10]. The outcomes of many experiments have shown that IP6 broad spectrum activities involve its impact on various intracellular signaling pathways, such as PI3K/AKT (Phosphatidylinositol-3 Kinase/AKT Serine/Threonine Kinase 1) [11,12] and expression of genes encoding key cellular proteins like p53, p21, p27, BCL-2, and MMPs [13,14,15,16,17,18,19]. The anti-cancer properties of dietary IP6 have previously been demonstrated by both in vitro and in vivo experimental cancer models including, prostate, breast, bladder, and colon [10,12,13,15,16,19].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of studies have investigated the anti-cancer properties of IP6 [ 56 , 57 , 58 ] ( Table 1 ). IP6 and its derivatives, such as IP5, IP4, and IP3, have been shown to possess anti-cancer activities by modulating biological processes implicated in various cancers, including inflammation, apoptosis, angiogenesis, proliferation, cell signaling, and gene expression [ 31 , 113 , 114 ]. Some studies have highlighted the potential cytostatic and cytotoxic properties of IP6 in malignant cells [ 59 , 115 , 116 ] ( Table 1 ).…”
Section: Anti-cancer Activity Of Ip6mentioning
confidence: 99%
“…The potential beneficial effects of exogenous IPs in cancer might go beyond their inhibition of PIs-mediated processes. For instance, Ins P 6 has been reported to have anti-cancer activity in several in vitro and in vivo models [ 65 ], including prostate [ 66 , 67 , 68 ], breast [ 69 , 70 ], bladder [ 71 ] and colon [ 72 , 73 ] cancer. Some very preliminary clinical results are also appearing [ 65 ].…”
Section: Exploiting the Binding Properties Of Ips For Therapeutic mentioning
confidence: 99%